2015
DOI: 10.1007/s10120-015-0486-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy treatment patterns, costs, and outcomes of patients with gastric cancer in the United States: a retrospective analysis of electronic medical record (EMR) and administrative claims data

Abstract: BackgroundThe aim of this study was to conduct a retrospective database analysis to describe the chemotherapy treatment patterns and outcomes of patients with gastric cancer.MethodsIndividuals diagnosed with gastric cancer were identified from the IMS Oncology Database, which contains electronic medical record (EMR) data collected from a variety of community practices, and the Truven Health MarketScan® Research database, an administrative claims database. Eligible patients were 18 years of age or older and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 7 publications
4
53
2
2
Order By: Relevance
“…Evaluated parameters were identified on the basis of previous reports with second-line or third-line CT [5,6,8,10], i.e., ECOG PS, age, response and PFS with first-line and second-line CT, and time interval from the start of first-line to the start of third-line CT. Continuous variables (first-line and second-line PFS and time from first-line to third-line therapy) were dichotomized according to the median values reported in the cohort.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Evaluated parameters were identified on the basis of previous reports with second-line or third-line CT [5,6,8,10], i.e., ECOG PS, age, response and PFS with first-line and second-line CT, and time interval from the start of first-line to the start of third-line CT. Continuous variables (first-line and second-line PFS and time from first-line to third-line therapy) were dichotomized according to the median values reported in the cohort.…”
Section: Methodsmentioning
confidence: 99%
“…As the benefit of second-line CT is demonstrated, there is a new window of opportunity for third-line treatments in selected cases, and at present it is estimated that about 20% of mGC patients receive third-line CT [5]. A retrospective analysis suggested that some clinicopathologic factors (PS, serum albumin level, histologic type, and PFS following second-line CT) might be helpful in identifying a subgroup of patients most likely to benefit from third-line treatment [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations may reflect the lack of standard treatment options during the study period of 2007 to 2013. Studies of advanced GEA, conducted in other geographies, demonstrated similar percentages of patients received second‐line therapy in the United States (Hess et al, ) and South America (de Alencar Camara Vieira et al, ; Novick et al, ), and higher percentages in East Asia (Carter et al, ; Hong et al, ). While treatment with fluoropyrimidine/platinum combinations is a recognised first‐line therapy for advanced GEA, as reflected in the 2016 ESMO guidelines, there are diverse chemotherapy options recommended after discontinuation of first‐line treatment.…”
Section: Discussionmentioning
confidence: 91%